Historical memory and collective identity: West Bank settlers reconstruct the past - Gabel, Ines (Media, Culture & Society, 2013)
Collective memory is a product of ideological construction that can be used as a key element in the elaboration of collective identity. This research will use the case study of Nekuda, the principal bulletin of the Jewish settlers in the West Bank, to explore the role played by a community paper in the construction of the community’s historical memory. This study is concerned with two main questions: first, which historical periods are reconstructed in the newspaper? The discourse deals with the continuity of Jewish presence in Israel since biblical times and reinforces the image of the Jewish victim in the Diaspora. The second question is how settlers’ historiography characterizes their collective identity. Settlers’ historical memory portrays a wide-ranging movement that includes unique features as well as a willingness to lead the whole nation together in search of an ordinary middle-class ambience. Collective memory situates the movement at the heart of the Zionist consensus, as a conservative rather than a revolutionary movement.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMTYzNDQzNzEyNDY3NTky